Carbon-coated silicon-carbon nanotube composite material and preparation method thereof
By adopting the preparation method of carbon-coated silicon-carbon nanotube composite, the problems of poor conductivity and unstable circulation performance of the negative electrode materials of existing lithium-ion batteries are solved, and higher capacity and longer life are achieved, while reducing production costs and realizing the recycling of waste resources.
Patent Information
- Application Number
- CN202510280591.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-06-10
AI Technical Summary
The existing lithium-ion battery negative electrode material, silicon-carbon composite, has poor conductivity, unstable circulation performance, and high material cost and complex process, which cannot meet the needs of higher capacity and longer life of lithium-ion batteries.
The carbon-coated silicon-carbon nanotube composite material was used to reduce the silicon particle size by wet ball milling method, and uniformly coated using medium and high temperature asphalt in xylene, combined with liquid-phase method to support the catalyst, and carbon nanotubes were grown by chemical vapor deposition method.
It improves the conductivity, cycle stability and ability to buffer silicon volume changes, reduces production costs, realizes the recycling of waste resources, and improves the capacity and life of lithium-ion batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of anode materials for lithium-ion batteries, and particularly to a preparation method of a carbon-coated silicon-carbon nanotube composite material. Background Art
[0002] Lithium-ion batteries have been applied to many fields in people's lives due to their advantages such as high capacity, long service life, and portability. As a key factor determining the capacity of lithium-ion batteries, the development of anode materials also affects the further development and popularization of lithium-ion batteries. Currently, the commercially applied anode material for lithium-ion batteries is graphite anode, but the theoretical specific capacity of graphite anode material is only 372 mAh g -1 , which can no longer meet people's demand for higher-capacity lithium-ion batteries. The theoretical specific capacity of silicon material is as high as 4200 mAh g -1 , about ten times more than that of graphite, and it has a low working voltage and extremely rich reserves in the earth's crust. It is a lithium-ion battery anode material with great application potential. However, silicon alone as an anode material has poor conductivity and will undergo a huge volume change during charge and discharge, continuously consuming the electrolyte, resulting in rapid capacity decay and low Coulomb efficiency of lithium-ion batteries. To solve the above problems, silicon-based materials are usually prepared into composite materials, but the specific capacity of current silicon-based composite materials is low, the cycle stability is poor, and the rate is low. To address these issues, silicon is mostly compounded with carbon materials with excellent conductivity to improve its conductivity and cycle performance. However, current silicon-carbon anode materials have poor conductivity, unstable cycle performance, high material cost, and complex processes. Therefore, it is crucial to develop silicon-carbon anode materials with excellent performance. Summary of the Invention
[0003] In view of this, an object of the present invention is to propose a carbon-coated silicon-carbon nanotube composite material and a preparation method to overcome the above problems.
[0004] A preparation method of a carbon-coated silicon-carbon nanotube composite material provided by the present application includes the following steps:
[0005] (1) Preparation of silicon suspension solution: Put polysilicon and an alcohol solvent into a zirconia ball milling tank and perform ball milling to form a silicon suspension solution;
[0006] (2) Preparation of asphalt xylene solution: Put asphalt into xylene, heat and stir, and obtain an asphalt xylene solution after suction filtration;
[0007] (3) Preparation of carbon-coated silicon composite material: Mix and disperse the silicon suspension solution and the asphalt xylene solution, and dry and carbonize the mixed dispersion liquid under the protection of an inert gas to obtain a carbon-coated silicon powder composite material;
[0008] (4) Preparation of carbon-coated silicon-carbon nanotube composite: Disperse the carbon-coated silicon powder composite in a metal salt solution to form a dispersion, and dry the dispersion to obtain a dry powder. Place the dried powder in a reaction furnace for chemical vapor deposition to obtain the carbon-coated silicon-carbon nanotube composite.
[0009] In the step (1), the mass ratio of polysilicon to milling beads is 1:1 - 10, the rotation speed of the ball mill is 500 - 1000 r / min, and the ball milling time is 4 - 6 h.
[0010] The polysilicon in the step (1) is the waste solar cell silicon wafer or integrated circuit silicon wafer that has been processed.
[0011] In the step (1), the alcohol solvent is ethanol or isopropyl alcohol, and the mass-volume fraction of polysilicon in the silicon suspension is 15 - 50%.
[0012] In the step (2), the mass-volume fraction of pitch is 4 - 6%.
[0013] The pitch in the step (2) is one or two of medium-temperature pitch and high-temperature pitch. The molecular weight of the aromatic alkane molecules in medium-temperature pitch and high-temperature pitch is larger, and the crystal structure of the derived carbon is more complete, having better conductivity. Preferably, the pitch in the step (2) is high-temperature pitch.
[0014] In the step (2), the heating temperature is 50°C - 70°C, and the stirring time is 1.5 - 2.5 h.
[0015] The mass ratio of the polysilicon to the pitch is 1:1 - 3. The inert gas is nitrogen, helium or argon.
[0016] In the step (3), the carbonization temperature is 750 - 800°C, and the carbonization time is 1 - 2 h.
[0017] In the step (4), the metal solution is one or more of nickel nitrate, magnesium nitrate, iron nitrate, cobalt nitrate solutions, preferably nickel nitrate solution. The concentration of the metal solution is 0.05 - 0.1 mol / L, and the mass ratio of the carbon-coated silicon composite to the metal solution is 1:1 - 1.5.
[0018] In the step (4), the chemical vapor deposition temperature is 650 - 750°C, using hydrogen and argon as carrier gases, and the chemical deposition gas is one of ethylene, acetylene, propylene; the deposition time is 20 - 40 min.
[0019] Preferably, the chemical deposition gas in step (4) is propylene. The volume ratio of argon: hydrogen: propylene is 0.1~0.3:2.5~3.5:0.15~0.3. The flow rate of the mixed gas composed of the chemical deposition gas and the carrier gas is 1.5~2.5 L / min.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The method of wet ball milling can effectively reduce the particle size of silicon. The dispersion and coating effect of silicon in the obtained suspension are better. Moreover, using waste solar cell silicon wafers or waste integrated circuit silicon wafers as raw materials can effectively reduce production costs, realize the recycling of waste resources, and enable large-scale industrial production.
[0022] (2) Dissolving medium and high temperature pitch in xylene to remove impurities in the medium and high temperature pitch ensures the controllability of material components. At the same time, it can achieve uniform and stable coating of silicon particles, avoid direct contact between silicon powder and electrolyte, and effectively alleviate the volume expansion of silicon. The uniformly coated carbon layer also plays a good conductive role and improves the cycle stability of the material. Using medium and high temperature pitch as the coating material, the molecular weight of aromatic alkane molecules in the medium and high temperature pitch is larger, and the crystal structure of its derived carbon is more complete, with better conductivity.
[0023] (3) Using the liquid phase method to load metal catalysts on the carbon-coated silicon composite material, the distribution of the catalysts is more uniform and the catalyst particle size is smaller, resulting in a more uniform distribution of the deposited carbon nanotubes and a smaller tube diameter. This makes the conductivity, cycle stability, and ability to buffer silicon volume changes of the composite material better.
[0024] (4) Growing carbon nanotubes on the surface of the carbon-coated silicon composite material by chemical vapor deposition. The carbon nanotubes grow in-situ on the surface of the carbon-coated silicon, making the combination of the carbon nanotubes and the carbon-coated silicon substrate more stable, and improving the conductivity and structural stability of the material. Description of the Drawings
[0025] Figure 1 is a schematic diagram of the structure of the carbon-coated silicon-carbon nanotube composite material;
[0026] Figure 2 is the X-ray diffraction pattern (XRD) of the carbon-coated silicon-carbon nanotube composite material prepared in Example 1;
[0027] Figure 3 is the scanning electron microscope image (SEM) of silicon powder in Comparative Example 1 (a), pitch carbon-coated silicon in Comparative Example 2 (b), silicon-carbon nanotubes (CNTS) in Comparative Example 3 (c, d), and carbon-coated silicon-carbon nanotubes (CNTS) in Example 1 (e, f);
[0028] Figure 4 It is the differential thermal gravimetric analysis (TG) curve of the carbon-coated silicon-carbon nanotube composite prepared in Example 1;
[0029] Figure 5 It is the cycling curves of silicon powder in Comparative Example 1, silicon-carbon nanotube composite in Comparative Example 3, and carbon-coated silicon-carbon nanotube composite in Example 1 at 0.2 A / g.
[0030] Figure 6 It is the cycling curves of silicon powder in Comparative Example 1, silicon-carbon nanotube composite in Comparative Example 3, and carbon-coated silicon-carbon nanotube composite in Example 1 at 2 A / g.
[0031] Figure 7 It is the cycling curves of silicon powder in Comparative Example 1, silicon-carbon nanotube composite in Comparative Example 3, and carbon-coated silicon-carbon nanotube composite in Example 1 at different current densities. Detailed implementation manners
[0032] In order to make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] Example 1
[0034] (1) Preparation of silicon powder suspension: Put 50 g of silicon wafers into 200 mL of ethanol, add 200 g of zirconia balls, and then pour them into the ball mill jar of the ball mill for grinding. The grinding speed is 500 r / min, and the grinding time is 6 h to obtain a silicon powder suspension.
[0035] (2) Preparation of pitch xylene solution: Weigh 50 g of medium-temperature pitch and 50 g of high-temperature pitch, put them into 2000 mL of xylene solution, stir at 60 °C for 2 h, and then perform suction filtration. The filtrate is the pitch xylene solution.
[0036] (3) Preparation of carbon-coated silicon composite: Mix the silicon powder suspension and the pitch xylene solution, ultrasonicate for 1 h, and then stir at a high speed of 15000 r / min for 10 min for dispersion. The dispersion is dried and carbonized in a tube furnace under the protection of argon. The carbonization temperature is 800 °C, the heating rate is 1-2 °C / min, and the carbonization time is 2 h. After carbonization, the carbon-coated silicon composite is obtained.
[0037] (4)Preparation of carbon-coated silicon-carbon nanotube composite: The carbon-coated silicon composite was dispersed in a nickel nitrate solution with a concentration of 0.1 mol / L and the same mass as the carbon-coated silicon composite, ultrasonicated for 1 h, and then dispersed by high-speed stirring at 15,000 r / min for 10 min. The dispersion was heated to 100 °C and dried with stirring to obtain dry powder. The dried powder was placed in a tube furnace for chemical deposition. The deposition process was as follows: Under an argon atmosphere, the temperature was raised to 400 - 500 °C at a heating rate of 5 - 10 °C, held for 40 - 60 min, and during the holding period, a mixed gas of argon / hydrogen with a volume ratio of 1:0.5 was introduced. Then, under the protection of argon, the temperature was raised to 650 - 750 °C at a heating rate of 5 - 10 °C / min, and the deposition time was 20 - 40 min. During the deposition process, a mixed gas of argon / hydrogen / propylene with a volume ratio of 0.2:3:0.25 was introduced. After the reaction, it was cooled with the furnace to obtain the carbon-coated silicon-carbon nanotube composite.
[0038] Example 2
[0039] (1)Preparation of silicon powder suspension: 50 g of silicon wafers were placed in 200 mL of ethanol, 50 g of zirconia balls were added, and then it was poured into the ball mill jar for grinding at a grinding speed of 1000 r / min for 6 h to obtain the silicon powder suspension.
[0040] (2)Preparation of pitch xylene solution: 100 g of medium-temperature pitch and 50 g of high-temperature pitch were weighed and added to 2500 mL of xylene solution, stirred at 70 °C for 2.5 h, and then filtered. The filtrate was the pitch xylene solution.
[0041] (3)Preparation of carbon-coated silicon composite: The silicon powder suspension and the pitch xylene solution were mixed, ultrasonicated for 1 h, and then dispersed by high-speed stirring at 15,000 r / min for 10 min. The dispersion was dried and carbonized in a tube furnace under the protection of nitrogen. The carbonization temperature was 750 °C, the heating rate was 1 - 2 °C / min, and the carbonization time was 2 h. After carbonization, the carbon-coated silicon composite was obtained.
[0042] (4)Preparation of carbon-coated silicon-carbon nanotube composite: The carbon-coated silicon composite was dispersed in a nickel nitrate solution with a concentration of 0.05 mol / L and a mass 1.5 times that of the carbon-coated silicon composite, sonicated for 1 h, and then dispersed by high-speed stirring at 15000 r / min for 10 min. The dispersion was heated to 100 °C and dried with stirring to obtain a dry powder. The dried powder was placed in a tube furnace for chemical deposition. The deposition process was as follows: Under an argon atmosphere, the temperature was raised at a rate of 5-10 °C to 400-500 °C, held for 40-60 min, and a mixed gas of argon / hydrogen with a volume ratio of 1:0.4 was introduced during the holding period. Then, under the protection of argon, the temperature was raised to 650-750 °C at a rate of 5-10 °C / min, and the deposition time was 20-40 min. A mixed gas of argon / hydrogen / propylene with a volume ratio of 0.1:2.5:0.15 was introduced during the deposition process. After the reaction, it was cooled with the furnace to obtain the carbon-coated silicon-carbon nanotube composite.
[0043] Example 3
[0044] (1)Preparation of silicon powder suspension: 50 g of silicon wafers were placed in 200 mL of isopropanol, 500 g of zirconia balls were added, and then poured into the ball mill jar for grinding. The grinding speed was 500 r / min, and the grinding time was 6 h to obtain a silicon powder suspension.
[0045] (2)Preparation of asphalt xylene solution: 25 g of medium-temperature asphalt and 25 g of high-temperature asphalt were weighed and added to 1250 mL of xylene solution, stirred at 70 °C for 1.5 h, and then filtered. The filtrate was the asphalt xylene solution.
[0046] (3)Preparation of carbon-coated silicon composite: The silicon powder suspension and the asphalt xylene solution were mixed, sonicated for 1 h, and then dispersed by high-speed stirring at 15000 r / min for 10 min. The dispersion was dried and carbonized in a tube furnace under the protection of nitrogen. The carbonization temperature was 800 °C, the heating rate was 1-2 °C / min, and the carbonization time was 1 h. After carbonization, the carbon-coated silicon composite was obtained.
[0047] (4) Preparation of carbon-coated silicon-carbon nanotube composite: Disperse the carbon-coated silicon composite in a magnesium nitrate solution with a concentration of 0.1 mol / L and a mass 1.5 times that of the carbon-coated silicon composite, sonicate for 1 h, then disperse by high-speed stirring at 15000 r / min for 10 min. Heat the dispersion to 100 °C and dry while stirring to obtain dry powder. Place the dried powder in a tube furnace for chemical deposition. The deposition process is as follows: Under an argon atmosphere, heat at a heating rate of 5 - 10 °C to 400 - 500 °C, hold for 40 - 60 min, and introduce an argon / hydrogen mixed gas with a volume ratio of 1:0.6 during the holding period. Then, under the protection of argon, heat to 650 - 750 °C at a heating rate of 5 - 10 °C / min, with a deposition time of 20 - 40 min. During the deposition process, introduce an argon / hydrogen / propylene mixed gas with a volume ratio of 0.3:3.5:0.3. After the reaction, cool with the furnace to obtain the carbon-coated silicon-carbon nanotube composite.
[0048] Example 4
[0049] Replace the high-temperature pitch in Example 1 with medium-temperature pitch of the same weight, and keep other conditions unchanged to obtain the carbon-coated silicon-carbon nanotube composite.
[0050] Example 5
[0051] Replace the medium-temperature pitch in Example 1 with high-temperature pitch of the same weight, and keep other conditions unchanged to obtain the carbon-coated silicon-carbon nanotube composite.
[0052] Comparative Example 1
[0053] Preparation of silicon powder suspension: Put 50 g of silicon wafers into 200 mL of ethanol, add 200 g of zirconia balls, then pour them into the ball mill jar for grinding at a grinding speed of 500 r / min for 6 h to obtain a silicon powder suspension. Dry the silicon powder suspension to obtain silicon powder.
[0054] Comparative Example 2
[0055] (1) Preparation of silicon powder suspension: Put 50 g of silicon wafers into 200 mL of ethanol, add 200 g of zirconia balls, then pour them into the ball mill jar for grinding at a grinding speed of 500 r / min for 6 h to obtain a silicon powder suspension.
[0056] (2) Preparation of pitch xylene solution: Weigh 50 g of medium-temperature pitch and 50 g of high-temperature pitch, put them into 2000 mL of xylene solution, stir at 60 °C for 2 h, then filter by suction, and take the filtrate as the pitch xylene solution.
[0057] (3) Preparation of carbon-coated silicon composite material: The silicon powder suspension was mixed with the asphalt xylene solution, sonicated for 1 h, and then dispersed by high-speed stirring at 15,000 r / min for 10 min. The dispersion was dried and carbonized in a tube furnace under the protection of argon. The carbonization temperature was 800 °C, the heating rate was 1 - 2 °C / min, and the carbonization time was 2 h. The carbon-coated silicon composite material was obtained after carbonization.
[0058] Comparative Example 3
[0059] (1) Preparation of silicon powder suspension: 50 g of silicon wafers were placed in 200 mL of ethanol, 200 g of zirconia balls were added, and then poured into the ball mill jar for grinding. The grinding speed was 500 r / min, and the grinding time was 6 h to obtain the silicon powder suspension.
[0060] (4) Preparation of silicon-carbon nanotube composite material: The silicon powder suspension was dispersed in a nickel nitrate solution with a concentration of 0.1 mol / L, sonicated for 1 h, and then dispersed by high-speed stirring at 15,000 r / min for 10 min. The dispersion was heated to 100 °C and dried while stirring to obtain dry powder. The dried powder was placed in a tube furnace for chemical deposition. The deposition process was as follows: Under an argon atmosphere, with a heating rate of 5 - 10 °C, it was heated to 400 - 500 °C and held for 40 - 60 min. During the holding period, a mixed gas of argon / hydrogen with a volume ratio of 1:0.4 - 0.6 was introduced. Then, under the protection of argon, it was heated to 650 - 750 °C at a heating rate of 5 - 10 °C / min and reacted for 20 - 40 min. During the holding process, a mixed gas of argon / hydrogen / propylene with a volume ratio of 0.1 - 0.3:2.5 - 3.5:0.15 - 0.3 was introduced. After the reaction, it was cooled with the furnace to obtain the silicon-carbon nanotube composite material.
[0061] Test Example
[0062] Performance test of the negative electrode material: The negative electrode material, conductive carbon black (Super-P), and carboxymethyl cellulose (CMC) were weighed and mixed according to a mass ratio of 80:10:10. After grinding and stirring evenly, the slurry was coated on a copper foil to make an electrode; a lithium metal sheet was used as the counter electrode, the electrolyte was 1 M LiPF6 dissolved in ethylene carbonate (EC): diethyl carbonate (DEC) = 1:1 (volume ratio), and the additives were 2 wt% vinylene carbonate (VC) and 10 wt% fluoroethylene carbonate (FEC); the separator was Celgard 2325. After completion, the electrochemical performance test was carried out. The test results of each example and comparative example are shown in Table 1.
[0063] Table 1 Test Results of Examples and Comparative Examples
[0064] Sample <![CDATA[0.2A g -1 The initial discharge capacity for the first time (mAh g -1 )]]> <![CDATA[0.2A g -1 The initial charging capacity (mAh g -1 )]]> <![CDATA[0.2A g -1 The first Coulomb efficiency <![CDATA[2A g -1 Discharge capacity after 600 cycles of the lower cycle (mAh g -1 )]]> <![CDATA[4A g -1 Discharge capacity under (mAh g -1 )]]> Example 1 2005 1635.8 81.58% 283.3 383.5 Example 2 1942 1520.7 78.31% 230.7 341.9 Example 3 1874 1426.8 76.14% 204.8 310.6 Example 4 1906.7 1460.7 76.64% 260.8 343.7 Example 5 2114.7 1762.3 82.17% 271.5 358.7 Comparative Example 1 2757.2 2090.5 75.82% 96.1 (400 times) 13.3 Comparative Example 2 2215 1830.9 82.66% 192.2 174.1 Comparative Example 3 2405.4 1918.3 79.75% 207.6 191.7
[0065] Figure 2 XRD pattern of the carbon-coated silicon-carbon nanotube composite material in Example 1, which determines the microstructure and diffraction structure of the carbon-coated silicon-carbon nanotube composite anode material, indicating that carbon nanotubes have been deposited on the surface of the carbon-coated silicon composite material. Figure 3 SEM images of silicon powder (a) in Comparative Example 1, carbon-coated silicon composite material (b) in Comparative Example 2, silicon-carbon nanotubes (CNTs) (c and d) in Comparative Example 3, and carbon-coated silicon-carbon nanotube composite material (CNTs) (e, f) in Example 1. It can be seen from the figure that compared with directly loading carbon nanotubes on silicon powder, the carbon nanotubes deposited and grown after coating with pitch carbon layer are more uniform. Figure 5 Cycling curves of silicon powder, silicon / carbon nanotube composite material (silicon powder / CNT), and carbon-coated silicon-carbon nanotube composite material (silicon powder / pitch carbon / CNT) at 0.2 A / g. Figure 6 Cycling curves of silicon powder, silicon / carbon nanotube composite material (silicon powder / CNT), and carbon-coated silicon-carbon nanotube composite material (silicon powder / pitch carbon / CNT) at 2 A / g. It can be seen from the figure that under different current density conditions, the performance of the carbon-coated silicon-carbon nanotube composite material is superior to that of the silicon / nanotube composite material and silicon powder. At a current density of 0.2 A / g, the specific capacity of the carbon-coated silicon-carbon nanotube composite material can still reach more than 1000 mAh / g after 200 charge-discharge cycles. At a current density of 2 A / g, the specific capacity of the carbon-coated silicon-carbon nanotube composite material can still reach more than 300 mAh / g after 600 charge-discharge cycles. From Figure 7 it can be seen that after charge-discharge at different current densities, the carbon-coated silicon-carbon nanotube composite material exhibits the highest charge-discharge capacity and cycle stability, and the recovery degree of the charge-discharge capacity is the highest when the current density returns to 0.1 A / g. The above results indicate that the carbon-coated silicon-carbon nanotube composite material prepared by the present invention has good lithium storage performance.
[0066] For those of ordinary skill in the art to which the present invention pertains, several simple deductions or substitutions can be made without departing from the concept of the present invention, without the need for creative labor. Therefore, simple improvements made by those skilled in the art based on the disclosure of the present invention should fall within the protection scope of the present invention. The above embodiments are the preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made thereto shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated silicon-carbon nanotube composite material, comprising the following steps: (1) Preparation of silicon suspension solution: polycrystalline silicon and alcohol solvent are placed in a zirconia ball milling tank and ball milled to form a silicon suspension solution; (2) Preparation of asphalt xylene solution: Place asphalt in xylene, heat and stir, and filter to obtain the asphalt xylene solution; (3) Preparation of carbon-coated silicon composite material: mixing and dispersing the silicon suspension solution and the asphalt xylene solution, and drying and carbonizing the mixed dispersion under the protection of an inert gas to obtain a carbon-coated silicon composite material; (4) Preparation of carbon-coated silicon-carbon nanotube composite materials: The carbon-coated silicon powder composite material is dispersed in a metal salt solution to form a dispersion, the dispersion is dried to obtain a dry powder, and the dried powder is placed in a reaction furnace for chemical vapor deposition to obtain a carbon-coated silicon-carbon nanotube composite material.
2. The preparation method according to claim 1, characterized in that In the step (1), the mass ratio of polycrystalline silicon to ball milling beads is 1:1-10, the ball mill speed is 500-1000 r / min, the ball milling time is 4-6 h, the mass volume fraction of polycrystalline silicon in the silicon suspension is 15-50%, and the alcohol solvent is ethanol or isopropanol.
3. The preparation method according to claim 1, characterized in that: In the step (2), the mass volume fraction of the asphalt is 4-6%, the heating temperature is 50°C-70°C, and the stirring time is 1.5-2.5h; the asphalt is one or both of medium-temperature asphalt and high-temperature asphalt.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The asphalt is high-temperature asphalt.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the polysilicon to the asphalt is 1:1-3, and the inert gas is nitrogen, helium or argon.
6. The preparation method according to claim 1, characterized in that: In the step (3), the carbonization temperature is 750-800° C. and the carbonization time is 1-2 h.
7. The preparation method according to claim 1, characterized in that: In the step (4), the metal solution is one or more of a nickel nitrate solution, a magnesium nitrate solution, a ferric nitrate solution, and a cobalt nitrate solution. The concentration of the metal solution is 0.05-0.1 mol / L. The mass ratio of the carbon-coated silicon composite material to the metal solution is 1:1-1.
5.
8. The preparation method according to claim 7, characterized in that: The metal solution is a nickel nitrate solution.
9. The preparation method according to claim 1, characterized in that: In the step (4), the chemical vapor deposition temperature is 650-750° C., hydrogen and argon are used as carriers, and the chemical deposition gas is one or more of ethylene, acetylene, and propylene; and the deposition time is 20-40 minutes.
10. The preparation method according to claim 9, characterized in that: The chemical deposition gas is propylene, the volume ratio of argon:hydrogen:propylene is 0.1-0.3:2.5-3.5:0.15-0.3, and the flow rate of the gas is 1.5-2.5 L / min.